Understanding metacognitive inferiority on screen by exposing cues for depth of processing. (October 2017) - Sidi, Yael; Shpigelman, Maya; Zalmanov, Hagar; Ackerman, Rakefet
Abstract: Paper-and-pencil learning and testing are gradually shifting to computerized environments. Cognitive and metacognitive researchers find screen inferiority compared to paper in effort regulation, test performance, and extent of overconfidence, in some cases, with unknown differentiating factors. Notably, these studies used reading comprehension tasks involving lengthy texts, which confound technology-related and cognitive factors. We hypothesized that the medium provides a contextual cue which leads to shallower processing on screen regardless of text length, particularly when task characteristics hint that shallow processing is legitimate. To test this hypothesis, we used briefly phrased yet challenging problems for solving on screen or on paper. In Experiment 1, the time frame for solving the problems was manipulated. As with lengthy texts, only time pressure resulted in screen inferiority. In Experiment 2, under a loose time frame, the same problems were now framed as a preliminary task performed before a main problem-solving task. Only the initial task, with reduced perceived importance, revealed screen inferiority similarly to time pressure. In Experiment 3, we replicated Experiment 1's time frame manipulation, using a problem-solving task which involved reading only three isolated words. Screen inferiority in overconfidence was found again only under time pressure. The results suggest that metacognitive processes are sensitive to contextual cues that hint at the expected depth of processing, regardless of the reading burden involved. Highlights: Text-learning studies often find screen inferiority in knowledge and monitoring. Minimizing the reading burden, we used brief but challenging problem-solving tasks. Time pressure and framing the task as preliminary still yielded screen inferiority. Metacognitive processes are sensitive to hints at the expected processing depth. Eliminating screen inferiority is possible by cues calling for in-depth processing.